Solution of the Data Load Issue in Business Intelligence Tools: QlikView Live Case Study - Anil Kumar Prajapati; Yogesh Mishra; Saral Nigam; Pradeep Lakhare (Journal of Systems Engineering and Information Technology (JOSEIT), 2024)
To stand in the marketplace it very essential to extract and deal with high-performance and usable data for every industry. The traditional ways are too slow and they are not suitable for the current scenario. This document gives knowledge about the new trends in technology which used for the benefit of business in terms of analysis and reporting. The document contains a live case study of the problem faced by an organization and a holistic evaluation of how to overcome it with the help of new technology. The primary objective of this case study is to minimize the ideal time for accessing and/or extracting files from different sources in the QlikView Platform.